Enhancing optical fiber communication systems using repetition coding for improved signal fidelity and error reduction - Menezla, Fayssal; Bouregaa, Mouweffeq; Debbal, Mohammed; Benadla, Sarra (Oficyna Wydawnicza Politechniki Wrocławskiej, 2025)
In optical communication systems, mitigating transmission errors caused by channel noise remains a critical challenge. This paper proposes bit repetition coding as a simple and effective method to enhance signal fidelity at the receiver. Our approach achieves a significant reduction in the bit error rate (BER), with simulations showing a decrease from 10–3 to 10–10 as the repetition count increases from 3 to 7. Furthermore, the clarity of the received signal improves consistently, with errors approaching zero at optimal repetition levels. This balance between simplicity and performance demonstrates the potential of repetition coding as a robust solution to transmission noise. Beyond its practical benefits, the study opens new pathways for designing resilient optical communication systems and highlights the relevance of repetition coding in improving both system reliability and efficiency. Future research is encouraged to explore its integration into next-generation optical networks.
Optica Applicata, Vol. 55, 2025, nr 2, s. 207-224
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; optical communication systems; repetition coding; bit error rate; quality factor Q; error correction techniques; optical fiber transmission